Atribut Dewan dan Corporate Social Responsibility: Kinerja Keuangan sebagai Variabel Moderasi - Anita Anita; Eren Eren (Jurnal Ekonomi Akuntansi dan Manajemen, 2022)
Corporate Social Responsibility (CSR) disclosure has been an important aspect of assessing companies these days. Indonesian listed companies have begun to disclose CSR through sustainability reports because they understand the importance of CSR in improving company efficiency and reputation. CSR certainly cannot be separated from corporate governance, namely the attributes of the board. Therefore, the study was implemented with the aim of discovering the impact of board attributes on CSR with financial performance as a moderation variable. CSR in the study was measured using GRI standards. Researchers used associative causal research aimed at examining the relationship of the studied variables. Secondary data that formed in the quantitative approach were obtained from the annual and sustainability report of listed companies contained on the IDX website. Samples from the study were sorted out using the purposive sampling method which amounted to 52 companies. The study has managed to show that board independence had a significant influence on CSR. Financial performance as the moderating variable weakened the board size-CSR and CEO duality-CSR relationships. Study results can be utilized by readers and subsequent researchers in enriching the existing literature on CSR topics. Keywords: Corporate Social Responsibility, Board Attributes, Sustainability Report, Financial Performance